Image of a city - Comparison of Bratislava and Prague - Šišková, Dominika; Postler, Milan, 1960-; Mikeš, Jiří, 1942-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
This master thesis deals with the importance of the destination image in general as well as with the image of the two selected cities, Bratislava and Prague. The goal of this thesis was to provide a sufficient evidence in order to identify the city with the better perceived image among tourists. In order to reach the ultimate goal, a field research targeting tourists who visited both cities at least once, was conducted. The results of the survey indicated that destination image of the two cities was influenced by the prior visitation and country of residence. In addition, the findings revealed that the perceived image of Prague is more positive than the image of Bratislava.
Vedoucí práce: Milan Postler
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses